IMPACT OF PAKISTAN-NIGERIA DEFENSE COOPERATION ON THE NIGERIAN ARMED FORCES - Okhogbe, Adekunle James (Journal of Terrorism Studies, 2025)
The study examined the impact of Pakistan-Nigeria Defense Cooperation on the Nigerian Armed Forces. The study utilized a descriptive survey and documentary research design to provide a comprehensive analysis of the cooperation’s dimensions. The target population comprised serving personnel across the Nigerian Armed Forces, including the Army, Navy, and Air Force, estimated at approximately 20,000 members nationwide. Using the Taro Yamane sample size determination technique, a sample size of 400 respondents was drawn from this population. Primary and secondary data collection methods were applied. Descriptive statistics and multiple linear regression analysis were employed to analyze the data. The findings revealed that Pakistan-Nigeria Defense Cooperation demonstrated the strongest impact on defense partnership effectiveness. Defense Technology Transfer also played a crucial role that sharing advanced military technology strengthened the ties between the two countries’ armed forces. Additionally, Joint Military Exercises contributed positively that coordinated training improved operational coordination and preparedness. In conclusion, the study established that Pakistan-Nigeria Defense Cooperation substantially improved the Nigerian Armed Forces’ effectiveness by fostering deeper collaboration, enhancing technological capabilities, and promoting joint operational readiness. The study recommended that Defense Ministry should strengthen long-term defense agreements with Pakistan to ensure sustained capacity-building programs.